2014
DOI: 10.17511/ijmrr.2014.i03.03
|View full text |Cite
|
Sign up to set email alerts
|

Study of serum cholinesterase, CPK and LDH as prognostic biomarkers in organophosphorus poisoning

Abstract: Introduction: Organophosphorus insecticides are arguably one of the commonest causes of morbidity and mortality due to poisoning worldwide, especially in developing countries like India due to its easy availability. This study was conducted to estimate the levels of Serum Cholinesterase, Serum Creatinine Phosphokinase & Serum Lactate Dehydrogenase on admission for correlation with severity of organophosphate poisoning and to reevaluate their levels on Day 4 and Day 8 and correlate them with the complications a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 13 publications
6
25
0
Order By: Relevance
“…This study revealed that there was nonsignificant difference between patients who developed respiratory failure and those who didn't as regard serum pseudocholinesterase level measured at 4 th day of poisoning. These results were in parallel with that of Sen et al (2014) who mentioned that Serum pseudocholinesterase serves as a diagnostic parameter for OP poisoning but it cannot be used as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This study revealed that there was nonsignificant difference between patients who developed respiratory failure and those who didn't as regard serum pseudocholinesterase level measured at 4 th day of poisoning. These results were in parallel with that of Sen et al (2014) who mentioned that Serum pseudocholinesterase serves as a diagnostic parameter for OP poisoning but it cannot be used as a prognostic biomarker.…”
Section: Discussionsupporting
confidence: 79%
“…These results supported by Sen et al (2014) who found that serum levels of LDH showed non significant difference between patients with acute OP poisoning who developed serious complications which end in death and those who showed complete clinical recovery. According to these results, they concluded that LDH is not a reliable indicator for prognosis and prediction of severe complications including respiratory failure.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…But all these assays are dependent on specialized laboratories and costly. So cheap and easily measurable biomarkers having prognostic value is the need of the hour (Sen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various prognostic tools such as serum creatine phosphokinase (CPK), lactate dehydrogenase (LDH), serum immunoglobulins, and circulating complements for early detection of patients at high risk for developing respiratory failure have been tried. [ 9 ] There will be the elevation of serum CPK in OP poisoning due to myonecrosis caused by persistent depolarization at the neuromuscular junction and oxidative cellular damage to muscle membrane. [ 10 11 ] Serum CPK level has also been studied as a predictor for the onset of IMS, but in earlier studies CPK has been measured only at admission and/or prior to discharge.…”
Section: Introductionmentioning
confidence: 99%